Convective Drying of Osmo-Treated Abalone (Haliotis rufescens) Slices: Diffusion, Modeling, and Quality Features - Roberto Lemus-Mondaca; Sebastian Pizarro-Oteíza; Mario Perez-Won; Gipsy Tabilo-Munizaga (Journal of Food Quality)
The focus of this research was based on the application of an osmotic pretreatment (15% NaCl) for drying abalone slices, and it evaluates the influence of hot-air drying temperature (40–80°C) on the product quality. In addition, the mass transfer kinetics of salt and water was also studied. The optimal time of the osmotic treatment was established until reaching a pseudo equilibrium state of the water and salt content (290 min). The water effective diffusivity values during drying ranged from 3.76 to 4.75 × 10−9 m2/s for three selected temperatures (40, 60, and 80°C). In addition, experimental data were fitted by Weibull distribution model. The modified Weibull model provided good fitting of experimental data according to applied statistical tests. Regarding the evaluated quality parameters, the color of the surface showed a change more significant at high temperature (80°C), whereas the nonenzymatic browning and texture showed a decrease during drying process mainly due to changes in protein matrix and rehydration rates, respectively. In particular, working at 60°C resulted in dried samples with the highest quality parameters.